Active and Passive Demethylation of Male and Female Pronuclear DNA in the Mammalian Zygote - Guo, Fan; Li, Xianlong; Liang, Dan; Li, Tong; Zhu, Ping; Guo, Hongshan; Wu, Xinglong; Wen, Lu; Gu, Tian-Peng; Hu, Boqiang; Walsh, Colum P.; Li, Jinsong; et al. (Cell stem cell, 2014)
The epigenomes of mammalian sperm and oocytes, characterized by gamete-specific 5-methylcytosine (5mC) patterns, are reprogrammed during early embryogenesis to establish full developmental potential. Previous studies have suggested that the paternal genome is actively demethylated in the zygote while the maternal genome undergoes subsequent passive demethylation via DNA replication during cleavage. Active demethylation is known to depend on 5mC oxidation by Tet dioxygenases and excision of oxidized bases by thymine DNA glycosylase (TDG). Here we show that both maternal and paternal genomes undergo widespread active and passive demethylation in zygotes before the first mitotic division. Passive demethylation was blocked by the replication inhibitor aphidicolin, and active demethylation was abrogated by deletion of Tet3 in both pronuclei. At actively demethylated loci, 5mCs were processed to unmodified cytosines. Surprisingly, the demethylation process was unaffected by the deletion of TDG from the zygote, suggesting the existence of other demethylation mechanisms downstream of Tet3-mediated oxidation. [Display omitted] •Maternal and paternal genomes both undergo active demethylation in mouse zygotes•Both zygotic genomes also undergo replication-dependent passive demethylation•At actively demethylated loci, 5mCs are processed to unmodified cytosines•Active demethylation depends on Tet3 dioxygenase, but not on TDG glycosylase In one-cell mouse embryos, the maternal and paternal genomes both undergo global Tet3-dependent active demethylation and replication-mediated passive demethylation. Surprisingly, the active demethylation pathway does not require TDG.